THE EFFECT OF MOTIVATION, SELF EFFICACY, TRINGA AND UNDERSTANDING OF PMK NUMBER 111/PMK.03/2014 ON CAREER INTEREST OF ACCOUNTING STUDENTS AS TAX CONSULTANTS - Sri Ayem; Ryan Hidayat (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
This study aims to examine the effect of motivation on the interest of accounting students in a career as a tax consultant, the effect of self-efficacy on the interest of accounting students in a career as a tax consultant, the effect of Tri-Nga on the interest of accounting students in a career as a tax consultant, and the effect of understanding on the regulation of the minister of finance number 111. /PMK.30/2014 on the interest of accounting students to have a career as tax consultants with a case study of students at the University of Sarjanawiyata Tamansiswa especially the Accounting Study Program The sample used in this study was UST Accounting students class 2017 – 2018 with a sampling technique using snowball sampling. The data obtained in this study are in the form of responses from respondents by filling out questionnaires that have been distributed via google form with a total sample of 109 respondents. The research data was processed using IBM SPSS 22 software, with data quality methods using validity and reliability tests, while the data analysis method used descriptive statistical tests and classical assumption tests consisting of: normality test, multicollinearity test, and heteroscedasticity test, and to test the hypothesis in this study using multiple linear analysis, coefficient of determination (R2), and partial test (t test). Based on the data processing that has been carried out in this study, it shows that motivation has a positive effect on the interest of accounting students to have a career as tax consultants. Self efficacy has a negative effect on the interest of accounting students in a career as a tax consultant. Tri-Nga has a positive effect on the interest of accounting students to have a career as a tax consultant. Understanding of the regulation of the minister of finance number 111/PMK.30/2014 has a negative effect on the interest of accounting students to have a career as tax consultants.